Edukasi Kesehatan Pola Hidup Sehat dan Pencegahan Penularan COVID-19 sebagai Upaya Peningkatan Kesehatan Lansia - Rusna Tahir; Muhaimin Saranani; Sahmad Sahmad (Poltekkes Kemenkes Kendari, 2022)
The COVID-19 pandemic has had a global impact on various aspects of life, especially the health of the elderly. This Community Service aims as an effort to increase the knowledge of the elderly regarding a healthy lifestyle and the prevention of transmission of COVID-19. The method used is health education. Community Service involves the participation of the elderly who are members of the Posyandu group for the elderly in Bungkutoko Village, Nambo Health Center Work Area, a total of 30 elderly. Community Service was enthusiastically attended by all participants and showed that health education is always important to implement as an effort to improve a healthy lifestyle and prevent COVID-19 by the elderly.